Prevalence and risk factors of inadequate medicine home storage: a community-based study - Martins, Rand Randall; Farias, Andreza Duarte; Oliveira, Yonara Monique da Costa; Diniz, Rodrigo dos Santos; Oliveira, Antonio Gouveia (Revista de Saúde Pública, 2017)
OBJECTIVE: Assess the extent of inadequate home storage of medicines andidentify important risk factors. METHODS: A cross-sectional survey based on a probability sample in the community, conducted in 267 households in Cuité, State of Paraíba, Northeast Brazil, in 2014. Logistic regression was used to study the risk factors. RESULTS: The prevalence of households with inadequate storage was 76.0%. Problems with storage include direct exposure to sunlight in 10.9% of households, the presence of dust in 23.6%, and storage within reach of children in 76.0%. Medications no longer used are usually disposed of into the environment in 92.1% of households. Inadequate storage is more likely when home organization of medications is the responsibility of a male subject (OR = 1.729) or an older person (OR = 1.029), when out of date medicines are found (OR = 2.963), and in households with no children (OR = 2.088). CONCLUSIONS: Physicians and pharmacists should advise patients on how to adequately store medicines at home, especially when the person in charge of medications is a male or an older adult, and if there are no children in the household.